(untitled) (Annals of Medical Research, 2023)
Aim: To present the first 60 supine percutaneous nephrolithotomy (PCNL) surgeries performed in our clinic with regard to the results and reliability of this surgery. Material and Methods: A retrospective study carried out on 60 patients who had undergone PCNL in supine position due to the kidney stone between September 2021 and May 2022. The following parameters were studied: Demographic characteristics, stone size and HU index, operation time and postoperative complications. Results: Patient’s mean age was 48.47, the oldest one was 90 years old, and 20 of them were female. Three of the patients had solitary kidney and 23 of them had previous surgery for kidney stone. 10 patients had this surgery under spinal anesthesia. Mean stone surface area and Hounsfield Unit were 590.55 mm2 and 903.52, respectively. In 3 cases, endoscopic combined intrarenal surgery was performed. Mean operation time was 63,75 minutes and scopy time was 16.5 seconds. 33 patients had totally tubeless procedure and 37 patients had tubeless surgery. None of the patient was required to blood transfusion or any other approach related to bleeding. Only two patients had fever and needed IV antibiotics. Stone free rate was 95 % in one session. Conclusion: Supine PCNL surgery is a feasible surgery with low complication rate and high stone-free rate. It is easier to switch to the supine position in clinics where this surgery is performed intensively in the prone position. It should become more widespread especially in terms of the advantages it offers compared to prone PCNL.